Dams and canyons disrupt gene flow among populations of a threatened riparian plant. (12th September 2014) - Werth, Silke; Schödl, Michael; Scheidegger, Christoph
Summary Natural and man‐made barriers have a significant impact on the population structure and genetic diversity of aquatic species. Little is known whether terrestrial, riparian species are affected in the same way by barriers. Here, we analysed the genetic structure of a threatened riparian shrub based on 20 microsatellite markers and 1176 individuals collected from 34 localities in four Alpine rivers in Europe (Isar, Lech, Rhine and Tagliamento). The catchments comprised a variety of potential barriers to gene flow for terrestrial riparian plants: dams, channelised stretches of river and canyons. We compared the average level of genetic differentiation (pairwise FST) between connected localities and localities isolated by natural or man‐made barriers. Genetic differentiation was higher between localities isolated by a barrier than between connected localities, indicating genetic isolation caused by barriers. This increased degree of genetic differentiation across barriers was evident in geographic tree models. Our results demonstrate genetic isolation effects due to large dams in a characteristic plant of Central European floodplains, highlighting that these types of barriers may negatively impact riparian plant populations. We also found genetic isolation effects in populations separated by natural barriers (canyons). These results have important implications for understanding the dynamics of riparian plant populations and for designing suitable management strategies for an effective conservation of riparian plants.